Begriffsverdrängung y Libertad de Religión. Notas sobre interpretación en derecho privado - Tolone Azzariti, Salvatore (2020)
ABSTRACT: Religious exemption in the United States is briefly analyzed by the effects of its conceptual lack on the system and its operational field. The application in private law, as a phase of the interpretation that develops control over the effects of the norm. Then the taxonomy of the fields further highlights these effects at a systematic level. The Private Law approach allows us to demonstrate the conceptual displacement that is generated by the First Amendment concerning other application fields and the classificatory function that, about the exemption, can be developed through the concept of the individual situation.   KEYWORDS: Religious exemption, fundamental rights, private law interpretation, subjective situation.   RESUMEN: La exención religiosa en los Estados Unidos es brevemente analizada por los efectos de su carencia conceptual, sobre el sistema y su ámbito operativo. La aplicación en el derecho privado, en cuanto fase de la interpretación que desarrolla el control sobre los efectos de las normas y la taxonomía de los ámbitos, aún más resalta estos efectos a nivel sistemático. El enfoque iuprivatístico permite evidenciar el desplazamiento conceptual que se genera por parte de la Primera Enmienda en relación a otros ámbitos aplicativos y la función de clasificación que, con respecto a la exención, puede ser desarrollado por medio del concepto de situación subjetiva.   JEL CODE / CLASIFICACIÓN JEL: Z12